Extracting large photovoltages from a-SiC photocathodes with an amorphous TiO2 front surface field layer for solar hydrogen evolution1. Issue 5 (6th May 2015) - Digdaya, Ibadillah A.; Han, Lihao; Buijs, Thom W. F.; Zeman, Miro; Dam, Bernard; Smets, Arno H. M.; Smith, Wilson A.
<x xml:space="preserve">Abstract</x> A p–i–n junction photocathode made from 110 nm (p/i) amorphous SiC and an (n) TiO2 top layer leads to an onset potential of +0.8 VRHE and a photocurrent density of 8.3 mA cm−2 at 0 VRHE using only earth abundant materials.